2018
DOI: 10.1002/adfm.201807555
|View full text |Cite
|
Sign up to set email alerts
|

Specific Biosensing Using DNA Aptamers and Nanopores

Abstract: The multiplexed biosensing of target molecules with high specificity and accuracy is of fundamental importance in both biological research and medical diagnostics. In this paper, the working range of the recent nanopore-DNA carrier based method is extended by introducing a two-step assay using specific DNA aptamers. A signal translation step allows for binding of the target in physiological conditions before the nanopore measurements. Using protein encoded DNA carriers, the simultaneous detection of three targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 43 publications
(55 reference statements)
0
41
0
Order By: Relevance
“…Recent research has showcased the potential of nanopores to detect molecular features along a DNA carrier strand, including proteins such as anti‐DNA antibodies and streptavidin, single‐stranded versus double‐stranded regions of a molecule, DNA‐hairpins, and aptamers . Potential applications range from digital information storage, multiplexed sensing, and genomic and/or functional genomic applications including genome mapping and epigenetics .…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has showcased the potential of nanopores to detect molecular features along a DNA carrier strand, including proteins such as anti‐DNA antibodies and streptavidin, single‐stranded versus double‐stranded regions of a molecule, DNA‐hairpins, and aptamers . Potential applications range from digital information storage, multiplexed sensing, and genomic and/or functional genomic applications including genome mapping and epigenetics .…”
Section: Introductionmentioning
confidence: 99%
“…It consists in the labeling of long DNA strands with spatially controlled markers, giving a specific current signal with recognizable intra-events. The combination of this technique with aptamers has allowed the detection of ATP [ 169 , 170 ] and proteins [ 157 , 170 ]. In 2017, a double-stranded DNA scaffold assembly with an aptamer protrusion has been used for the specific detection of ATP [ 169 ].…”
Section: Nanopores and Aptamers: A Winning Combinationmentioning
confidence: 99%
“…Finally, they performed this strategy in human serum, demonstrating the flexibility and the efficiency of this bar-coding aptamer detection even in complex sample. Another study has shown the feasibility of using this technique for the simultaneous detection of three different targets on the DNA carrier: ATP, thrombin and lysozyme [ 170 ].…”
Section: Nanopores and Aptamers: A Winning Combinationmentioning
confidence: 99%
“…The DNA strands were then analyzed by similar protein encoded DNA carriers. [ 132 ] Overall, digitally encoded DNA carrier shows great potential in selective and multiplexed detection of proteins, since only 10 bits enable coding 2 10 = 1024 proteins. However, the molecule weight contrast between the binding site and the target analyte should be large enough to distinguish bound and unbound target.…”
Section: Selectivitymentioning
confidence: 99%